Regional and cellular organization of the autism-associated protein UBE3A/E6AP and its antisense transcript in the brain of the developing rhesus monkey - Gonzalez Ramirez, Chavely; Salvador, Sarah G.; Patel, Ridthi Kartik Rekha; Clark, Sarah; Miller, Noah W.; James, Lucas M.; Ringelberg, Nicholas W.; Simon, Jeremy M.; Bennett, Jeffrey; Amaral, David G.; Burette, Alain C.; Philpot, Benjamin D. (Frontiers in Neuroanatomy, 2024)
Angelman syndrome (AS) is a neurogenetic disorder caused by mutations or deletions in the maternally-inherited UBE3A allele, leading to a loss of UBE3A protein expression in neurons. The paternally-inherited UBE3A allele is epigenetically silenced in neurons during development by a noncoding transcript (UBE3A-ATS). The absence of neuronal UBE3A results in severe neurological symptoms, including speech and language impairments, intellectual disability, and seizures. While no cure exists, therapies aiming to restore UBE3A function—either by gene addition or by targeting UBE3A-ATS—are under development. Progress in developing these treatments relies heavily on inferences drawn from mouse studies about the function of UBE3A in the human brain. To aid translational efforts and to gain an understanding of UBE3A and UBE3A-ATS biology with greater relevance to human neurodevelopmental contexts, we investigated UBE3A and UBE3A-ATS expression in the developing brain of the rhesus macaque, a species that exhibits complex social behaviors, resembling aspects of human behavior to a greater degree than mice. Combining immunohistochemistry and in situ hybridization, we mapped UBE3A and UBE3A-ATS regional and cellular expression in normal prenatal, neonatal, and adolescent rhesus macaque brains. We show that key hallmarks of UBE3A biology, well-known in rodents, are also present in macaques, and suggest paternal UBE3A silencing in neurons—but not glial cells—in the macaque brain, with onset between gestational day 48 and 100. These findings support proposals that early-life, perhaps even prenatal, intervention is optimal for overcoming the maternal allele loss of UBE3A linked to AS.